Study of the influence of the application of ultra-high pressure homogenization (UAPH) and [Ca ++ ] on the stability of rice milk (INNOTEC, 2012)
Designed rice milk formulations were submitted to different thermal treatments and UHPH treatments. Particle size profiles were measured and related to physicochemical stability. The samples processed by UHPH showed higher stability than milk processed thermally only. From the study of the interaction between micronutrients (Ca++) and rice proteins it was found that increasing Ca++ concentration up to 80 ppm decreases the stability of the beverage to a minimum. For UHPH treated samples (inlet temperature 85 ºC, 300 MPa valve temperature 135 ºC) and UHT (142 ºC 6 s), total counts, spores, Bacillus Cereus and Enterobacteriaceaes remained all below the detection limit of 1 UFC/mL. UHPH and UHT samples were incubated at 30 °C for two weeks without microbial growth or alteration. UHPH proved to be a valid technology to stabilize and preserve rice milk by reducing particle size below 1 µm and reducing spoiling bacteria.
Keywords: Vegetable drink; UHPH; rice; stability